Hadis dan Ulumul Hadis serta Urgensinya dalam Pendidikan Islam - Elvi Silvia (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article aims to analyze Hadith and Ululmul Hadith and their importance in Islamic education. This research uses the library research method with documentation data collection techniques. The primary data used in this research is Hadith. The secondary (complementary) data used are books and articles related to Hadith and ulumul Hadith and their relation to education. The results of this research are that hadith is something that is attributed to the Prophet Muhammad SAW in the form of words, actions, taqrir (decrees) and ulumul hadith is the science of rules for knowing the condition of sanad and matan. The urgency of hadith plays a very important role in the development of educational sciences, especially in the field of Islamic education where hadith is a special explanation of the Koran that cannot be refuted and the Koran is the basis of sharia which is very comprehensive in nature. So if you only use the basics of the Koran without further explanation, there will be many problems that cannot be resolved or will cause confusion that cannot be resolved.